Maternal Mortality and Related Obstetric Risk Factors at A Tertiary Care Hospital of Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: To calculate maternal mortality ratio and evaluation of its associated obstetric risk factors in our set up.Study Design: Cross sectional studySetting: Obstetrics and Gynaecology unit 4, Sir Ganga Ram Hospital Lahore from January 2013 to June 2015 (2 and half years).Materials and Methods: All maternal deaths in antenatal/ intrapartum and postpartum period within 42 days after delivery were studied during the study period, while accidental or incidental causes of death were not included in the study. All the  data was recorded on proformawhich was already designed containing variables i.e maternal demographics, pregnancy related risk factors and other information.All received dead mothers were excluded.Results: A total number of 21811 delivered women were calculated for maternal deathsout of which, there were 51 deaths giving a Maternal Mortality Ratio of 233.8/100,000 live births. Among these 100% were unbooked. Commonest risk factors were anemia (25.4%) heart disease (21.5%), hypertensive disorders of pregnancy (17.6%), post partumhaemorrhage(13.7). Third most common risk factor found was hypertensive pregnancy disorder i.eeclampsia, HELLP syndrome.Conclusion: This maternal mortality ratio is quite less than the world wide figure because of prompt diagnosis and early intervention, but the main reason for this figure which is still very high because antenatal and pre-pregnancy care was not obtained which, if it is there most of the risk factors can be early picked up and managed accordingly.
Keywords: Maternal Mortality, Risk Factors